Concurrent Treatment with BCNU and Gamma Knife Radiosurgery in the Rat Malignant Glioma Model - Cho, Keun-Tae; Kim, Dong Gyu; Paek, Sun Ha; Chung, Hyun-Tai; Jung, Hee Won; Park, Hyung Woo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Background Radiosurgery has been shown in a randomized trial not to provide any survival benefit for newly diagnosed glioblastoma multiforme (GBM). Nevertheless, several institutional retrospective series have supported the role of radiosurgery as an adjuvant therapy in GBM. The purpose of this study was to investigate the efficacy of concurrent therapy with 1,3 bis[2-chloroethyl]-1-nitrosourea (BCNU; carmustine) and Gamma Knife radiosurgery (GKRS; Gamma Knife® Model C, Elekta AB, Stockholm, Sweden) in the C6 rat glioma model. Taken together, new therapeutic strategies other than the simple addition of radiosurgery deserve to be investigated in the interest of enhancing the effects of radiosurgery.Material and Methods C6 glioma cells of 5 × 105 were stereotactically implanted into Sprague-Dawley rats. Tumor volume was measured 2 weeks later using brain magnetic resonance (MR) imaging and rats were treated with BCNU (7 mg/kg, intraperitonial injection), GKRS (20 Gy at 50% isodose line), or BCNU followed by GKRS at a 1.5-hour interval. The six surviving rats in each group were sacrificed, 2 weeks after treatment. Tumor volume was measured in the tissue sections and compared with that measured via MR imaging. Percent volume growth was calculated and categorized into one of four groups: progressive disease, stable disease, partial response, or complete response.Results Tumor volume significantly increased in all six rats in the control group and decreased in all six rats in the BCNU + GKRS group after treatment. Better tumor control was observed in the BCNU + GKRS group compared with the control, BCNU, and GKRS groups on linear-by-linear association analysis and Fischer's exact test.Conclusions We suggest that concurrent treatment with BCNU and GKRS is more effective in local tumor control compared with GKRS or BCNU alone, in the C6 rat glioma model.
Keywords: glioblastoma multiforme; 1,3 bis[2-chloroethyl]-1-nitrosourea (BCNU); C6 rat glioma model; gamma knife radiosurgery; local tumor control